Alexander Philipoff, Nina Verchinina, Edouard Borovansky, Colonel Wassily de Basil, Olga Morosova and Tatiana Stepanova (left to right) watching a students performance - Pearl, S. Alston (1940)
Several people in the photograph were part of the Original Ballet Russe.
Title devised by cataloguer based on caption list prepared by researcher.
Photographer's stamp on reverse.
Condition: Fair.
Part of the collection: Geoffrey Ingram archive of Australian ballet.
Also available online
Keywords: Borovansky Ballet -- Photographs; Ballets russes du Col. W. de Basil -- Photographs; Ballet dancers -- Photographs; Ballet -- Study and teaching -- Australia -- Photographs